ANALYSIS OF USING EFFICIENT LOGGING TOOLS AT PT. PURWA PERMAI IN CENTRAL KALIMANTAN - Sona Suhartana; Yuniawati Yuniawati (Indonesian Journal of Forestry Research, 2008)
A high log demand that often exceeds its supply capability should be overcome by using appropriate logging  tools. Numerous  kinds and types of logging  tools require  a well planning in their utilization. Number of tools which are greater or fewer than what is actually needed can be disadvantageous  for a company. In relevant to these aspects, a study was carried out at a timber estate in Central Kalimantan  in 2007. The aim of the study was to find out an efficient number  of tools used for logging  in a timber  estate. The analysis was based on the target and realization of the company’s log production. The result revealed that: (1) Optimum number of logging tools depended on production target,  i.e. 41 units  of chainsaws  for felling,  42 units  of farm tractors  for skidding,  9 units of loaders for loading and unloading, and 36 units of trucks for transportation; (2) Number  of logging tools as obtained from all activities  in the field was fewer than that from  the analysis based on production target and realization. This condition  indicated that number of logging tools used in the company was not yet efficient.